Ibiza, Spanien. Zum antiken Bleiglanzabbau am Puig de s’Argentera - Hermanns, Marcus H. (e-Forschungsberichte des DAI, 2017)
In 2016 the work continued at the northern hill foot of the Puig de s’Argentera. The main aim was still to expand the terrain to be studied. Therefore, several campaigns took place during the first half of the year, first to uncover the entire terrain, mainly the deeper parts of the opencast mining, and then to record and to examine the unearthen relics of mining activities analysing their context and gaining further hints concerning their date. This project is part of DAI Cluster 2.